Asymmetry of the Matter-Anti Matter Ratio in the Universe and Violation of E=mc2: Sayed`s Theory for Matter-Antimatter Chirality and its Correlations - El-Mongy, Sayed (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Unity of the laws is a function in divinity of the Creator – Allah. The postulation of the Big Bang that the universe began by symmetrical matter to anti-matter (M/AM) ratio leads to non-matter universe. This article went deeply and simply through the asymmetry and imbalance of (M/AM) ratio at the beginning of the universe and in the time being. A simple derived formula (Sayed`s Matter-Antimatter ratio) quantified the Anti-matter percentage to be ¼ (~25%), while it was ¾ (~75%) for matter at the early universe. This ratio is almost equivalent ~π. It may be concluded that the asymmetry of (M/AM) is due to violation of E=mc2. Comparison of the published and a derived electron antineutrino/neutrino mass ratio was found to be correlated by Sayed`s factor (SF); about 30√πe. The entropy of black hole is inversely correlated with antimatter percentage and (~3/4π). The proton/electron and antineutrino/neutrino mass ratios correlated with their acceleration were also expressed. Based on our current and previous published findings; the ratios of dark energy/dark matter = Hydrogen/Helium = Matter/antimatter ≈π.